2014
DOI: 10.1128/jvi.00657-14
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Residues at the Carboxyl Terminus of the Herpes Simplex Virus 1 UL20 Membrane Protein Regulate Cytoplasmic Virion Envelopment and Infectious Virus Production

Abstract: The herpes simplex virus type 1 (HSV-1) UL20 gene encodes a 222-amino-acid nonglycosylated envelope protein which forms a complex with viral glycoprotein K (gK) that functions in virion envelopment, egress, and virus-induced cell fusion. To investigate the role of the carboxyl terminus of the UL20 protein (UL20p) in cytoplasmic virion envelopment, a cadre of mutant viruses was constructed and characterized. The deletion of six amino acids from the carboxyl terminus of UL20p caused an approximately 1-log reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The intra- and extracellular titers of HSV1(17 + )Lox-ΔUL20 and -CheVP26-ΔUL20 were about 1,000-fold lower than their parental strains in non-complementing Vero cells, but higher in a pUL20 complementing cell line ( S2C and S2D Fig ). Similar results have been reported for HSV1-ΔUL20 mutants in other genetic backgrounds [ 25 , 26 , 54 56 ]. There were little differences between the parental Lox and the -CheVP26 strains, indicating that tagging VP26 with mCherry (Che) did not impair HSV-1 replication, as reported before [ 24 , 57 ].…”
Section: Resultssupporting
confidence: 89%
“…The intra- and extracellular titers of HSV1(17 + )Lox-ΔUL20 and -CheVP26-ΔUL20 were about 1,000-fold lower than their parental strains in non-complementing Vero cells, but higher in a pUL20 complementing cell line ( S2C and S2D Fig ). Similar results have been reported for HSV1-ΔUL20 mutants in other genetic backgrounds [ 25 , 26 , 54 56 ]. There were little differences between the parental Lox and the -CheVP26 strains, indicating that tagging VP26 with mCherry (Che) did not impair HSV-1 replication, as reported before [ 24 , 57 ].…”
Section: Resultssupporting
confidence: 89%
“…Firstly, we found that both ORF7 and ORF53 co-localized well with the TGN46 protein ( Figure 3A and 3B), which is widely used as a TGN marker in numerous studies (Barr et al, 2010;Donsante et al, 2011;Zhao et al, 2012;Charles et al, 2014;Nonnenmacher et al, 2015;Pillay et al, 2016). The Pearson's coefficients were 0.70 ± 0.09 and 0.68 ± 0.08 in the co-localized volume of TGN46 with ORF7 and ORF53, respectively (n = 10 in each group).…”
Section: Orf7 Co-localizes With Orf53 In the Tgn Of Infected Cellsmentioning
confidence: 79%
“…To assess the requirement of UL21 for these Syn mutants, we chose two syncytial mutations for each locus to test whether the absence of UL21 leads to a loss of fusion. For UL20, we used the syncytial substitutions R209A (37) and F222A (38), as these have been described as ones that are not associated with loss of viral titer in an otherwise wild-type background. For UL24, the syncytial substitutions were the E99A/K101A combination of changes and the singular point mutation G121A (39).…”
Section: Fig 2 Legend (Continued)mentioning
confidence: 99%